Behaviour of Reduced-Scale Fully Grouted Concrete Block Masonry Building - Vandervelde, Jordan (My University, 2010)
Much of the experimental research on shear wall elements in reinforced masonry has been performed on shear walls in isolation. These elements have typically been removed from their structural system and artificial idealized loading is placed on them. Testing is limited to these types of experiments because of limitations of laboratory equipment or the potential cost constraints of attempting tests on full building systems. Full-scale testing as well as some reduced scale testing has been performed at McMaster University over recent years. However, in order to examine larger walls as well as full building structures, the focus of research has turned more towards reduced-scale testing. First, half-scale tests were completed, and now, as part of a new test program, testing utilizes one-third scale concrete blocks.
This thesis focuses on the ductile response of a one-third scale reinforced, fully grouted, concrete block shear wall building. As the name implies, the lateral load resisting system consists solely of reinforced masonry shear walls. Documentation is presented of the building response in terms of stiffness, torsion and post-yielding lateral loading. Further examination is presented related to the diaphragm action and associated inter-wall coupling behaviour. The load-displacement characteristics of the structure are then broken down into the response of the individual shear wall elements within the structure. These response characteristics are then related back to previous studies of the same wall configurations tested in isolation.
The primary objective of the thesis is to provide a foundation to build a relationship between the behaviour of reinforced masonry shear walls tested in isolation and their behaviour in a building or system setting. This, along with future research in this area will provide comparisons between current design practice and observed performance for the purpose of potentially amending design practices related to seismic provisions as found in the National Building Code of Canada (2010) as well as the masonry design standard C5A 5304.1 (2004).
The results of this study show a positive response for the use of one-third scale testing as well as testing of full systems. Although relatively brittle reinforcing steel limited the ability of the structure to achieve the expected ductility level the test results did show excellent promise for the hypothesis presented. This experimental program showed the potential of reinforced masonry shear walls to resist seismic loading while acting as part of a structural system.
Keywords: Civil Engineering; Civil Engineering